Epigenetic deregulation of TCF21 inhibits metastasis suppressor KISS1 in metastatic melanoma - Arab, Khelifa; Smith, Laura T.; Gast, Andreas; Weichenhan, Dieter; Huang, Joseph Po-Hsien; Claus, Rainer; Hielscher, Thomas; Espinosa, Allan V.; Ringel, Matthew D.; Morrison, Carl D.; Schadendorf, Dirk; Kumar, Rajiv; et al. (Carcinogenesis, 2011)
Metastatic melanoma is a fatal disease due to the lack of successful therapies and biomarkers for early detection and its incidence has been increasing. Genetic studies have defined recurrent chromosomal aberrations, suggesting the location of either tumor suppressor genes or oncogenes. Transcription factor 21 (TCF21) belongs to the class A of the basic helix-loop-helix family with reported functions in early lung and kidney development as well as tumor suppressor function in the malignancies of the lung and head and neck. In this study, we combined quantitative DNA methylation analysis in patient biopsies and in their derived cell lines to demonstrate that TCF21 expression is downregulated in metastatic melanoma by promoter hypermethylation and TCF21 promoter DNA methylation is correlated with decreased survival in metastatic skin melanoma patients. In addition, the chromosomal location of TCF21 on 6q23-q24 coincides with the location of a postulated metastasis suppressor in melanoma. Functionally, TCF21 binds the promoter of the melanoma metastasis-suppressing gene, KiSS1 , and enhances its gene expression through interaction with E12, a TCF3 isoform and with TCF12. Loss of TCF21 expression results in loss of KISS1 expression through loss of direct interaction of TCF21 at the KISS1 promoter. Finally, overexpression of TCF21 inhibits motility of C8161 melanoma cells. These data suggest that epigenetic downregulation of TCF21 is functionally involved in melanoma progression and that it may serve as a biomarker for aggressive tumor behavior.